2D Prior Spreading Inspired from Chinese Xuan Papers. (24th May 2018) - Zheng, Shuang; Du, Ming; Miao, Weining; Wang, Dianyu; Zhu, Zhongpeng; Tian, Ye; Jiang, Lei
Abstract: Liquid spreading is fundamental to many applications in interfacial materials. However, anisotropic spreading inside superlyophilic fabrics, playing an important role in clothing materials, ink printing, medical masks, and paper manufacturing industry, is rarely studied. Here, a special wetting phenomenon is introduced on Chinese Xuan papers, a kind of handmade papers dating from thousands of years ago in China, mainly for painting and calligraphy with Chinese brushes. Different from other papers or porous materials, liquid, such as ink, prefers to spread along the 2D direction, meaning that liquid can spread out rapidly while it seldom permeates through the papers, avoiding blotting of the underlying sheet. The antipermeation test shows that 150 µL of water is added to Xuan papers without permeation, which is attributed to the multilayered spreading, resulting from the layered anisotropic micro/nanofibrous structures. Inspired from this, similarly structured fabrics with liquid 2D prior spreading and antipermeation abilities are electrospun. About 175 µL of water is able to spread completely without permeation. These findings demonstrate a new wetting concept for manufacturing antipermeation materials with controlled ultrafast 2D spreading properties. Abstract : Inspired by Chinese Xuan paper, two dimensional (2D) prior spreading is a special wetting phenomenon that layered micro‐ and nanostructures of such paper contribute to multi‐layered spreading behaviors. Fast spreading is facilitated on a 2D plane and liquid transportation is restrained along the normal direction, providing a new approach for fabricating materials with both anti‐permeation and fast spreading abilities.